The role of probiotics in the immune response and intestinal microbiota of children with celiac disease: a systematic review - Camila Fernanda Jedwab; Bruna Cardoso de Mattos Boccalini Roston; Ana Beatriz Ferreira de Souza Toge; Isadora Fagundes Echeverria; Guilherme Ojea Gomes Tavares; Matheus Alves Alvares; Vera Esteves Vagnozzi Rullo; Marcella Rocha Machado de Oliveira
ABSTRACT Objective: To evaluate changes in peripheral immunological response (decrease in blood proinflammatory cytokines) and fecal microbiota (especially Bacteroidetes and Firmicutes) after administration of probiotics in children with celiac disease on a gluten-free diet. Data source: The databases MEDLINE, LILACS, Springer and SciELO were used for this review, with the descriptors "celiac disease AND probiotics". At the end of the search, 168 articles were retrieved, four of which were included in the final qualitative synthesis, having as inclusion criteria randomized clinical trials and pediatric population (1-19 years) and, as exclusion criteria, interventions other than probiotics, studies with patients with other diseases associated with celiac disease, or patients who did not meet the diagnostic criteria. All elected studies were published until September 2020, without language restriction, with patients receiving strains of Bifidobacterium breve or B. longum and on a gluten-free diet. Data synthesis: The studies show that the administration of probiotics along with a gluten-free diet, can approximate the fecal microbiota of celiac patients to typical conditions of healthy individuals, by restoring the abundance of some microbial communities that characterize the typical physiological condition. In addition, the administration of probiotics can reduce serum proinflammatory cytokines (mainly TNF-alpha). Conclusions: Despite the positive correlation between probiotics and fecal microbiota/serological markers in pediatric patients with celiac disease, we emphasize the need for future multicentric studies that should include a larger number of patients and a longer follow up period.%